VIEWING LIFE THROUGH DEATH'S PERSPECTIVE: The Confluence of The Theravada Buddhism's Theology of Death with the Christian Faith - Kurniawan, Markus; Prihantoro, Yogi (QUAERENS: Journal of Theology and Christianity Studies, 2023)
Death is a very close thing in human life, even a certain thing. It is impossible to predict when this death will occur. Therefore, death is also part of a mysterious phenomenon that occurs repeatedly with the same subject, namely people. The saying that the closest friend is dead. Sooner or later, willingly, or not, every human being will experience death that no one can avoid. When it comes to reacting to death, some people are afraid, some are worried, and some sincerely accept it. This article uses descriptive – analysis using Zur Theologie des Todes – ‘On the Theology of Death,’ published in 1958. Karl Rahner developed his theological approach to death. Death, according to Rahner, is an event that affects the whole human being, not just the body, while the immortal soul remains fundamentally intact. According to the Buddhist concept, death is the end of suffering. Birth, dissatisfaction, pain, and dissatisfaction, are suffering in life. So, death is a possible way to reduce pain Death, which is seen as the end of one's life, should be seen as an act in itself. Rahner interprets fulfillment as belonging to death itself. Nonetheless, Rahner's theory, like Augustine's, continues to evolve, and his treatment of the "liberty of the sick," if wrong, offers an important addition to moral meditation on the issue of the end of life. Kematian adalah hal yang sangat dekat dalam kehidupan manusia, bahkan hal yang pasti. Mustahil untuk memprediksi kapan kematian ini akan terjadi. Oleh karena itu, kematian juga merupakan bagian dari fenomena misterius yang terjadi berulang kali dengan subjek yang sama, yaitu orang. Ungkapan yang mengatakan bahwa sahabat terdekat adalah kematian. Cepat atau lambat, rela atau tidak, setiap manusia akan mengalami kematian yang tidak dapat dihindari oleh siapa pun. Ketika datang untuk bereaksi terhadap kematian, beberapa orang takut, beberapa khawatir, dan beberapa dengan tulus menerimanya. Dalam Zur Theologie des Todes – On the Theology of Death, diterbitkan pada tahun 1958, Karl Rahner mengembangkan pendekatan teologisnya sendiri terhadap kematian. Kematian, menurut Rahner, adalah suatu peristiwa yang mempengaruhi seluruh manusia, bukan hanya tubuh, sementara jiwa yang tak berkematian secara fundamental tetap utuh. Menurut konsep agama Buddha, kematian adalah akhir dari penderitaan. Kelahiran, ketidakpuasan, rasa sakit, ketidakpuasan, adalah penderitaan dalam hidup. Jadi kematian adalah cara yang mungkin untuk mengurangi rasa sakit. Kematian yang dipandang sebagai akhir dari kehidupan seseorang, harus dilihat sebagai tindakan itu sendiri. Rahner menafsirkan pemenuhan sebagai milik kematian itu sendiri. Meskipun demikian, teori Rahner, seperti teori Agustinus, terus berkembang, dan perlakuannya terhadap "kebebasan orang sakit", jika salah, menawarkan tambahan penting bagi meditasi moral tentang masalah akhir hayat.